Clinico-epidemiology of arthropod stings and bites in primary hospitals of North Western province of Sri Lanka. (3rd October 2018) - Kularatne, Senanayake A. M.; Shahmy, Seyed; Rathnayake, Shantha S.; Dawson, Andrew H.
Abstract: Objective: Arthropod stinging and bites are common environmental hazards in Sri Lanka. However, their medical importance has not been fully evaluated yet. This study aims to study the burden, epidemiology, and outcome of stings and bites in primary hospitals in the Kurunegala district in North Western Province (NWP) of Sri Lanka. Methodology: The study was conducted one year from 25th May 2013 to 25th May 2014. Details of all stings and bites admissions and their outcomes were retrospectively extracted from hospital records in all 44 primary hospitals in the district. Results: There were 623 stings and bites with population incidence of 38/100, 000 (95% CI 27–52). There were no deaths. Median age was 38 years (IQR: 19–53 years), and 351 (56%) were males. Most of stings and bites (75%) occurred in the daytime. Median time to hospital arrival was 55 minutes (IQR: 30 min to 2 h). The offending arthropods had been identified in 557 (89%) cases, of them, 357 (57%) were Hymenoptera (hornet and bees), 99 centipedes, 61 spiders and 40 scorpions. Local pain occurred in 346 (56%) cases – centipede 69 (70%), Scorpion 24 (60%), spider 36 (59%), Hymenoptera 187 (52%) and unidentified 30 (45%). Hymenoptera stings and spider bites occurred between 06 am to 12 noon, and scorpion stings and centipede bites mostly occurred between 06 pm to 12 midnight. Mild, moderate to severe anaphylaxis reactions occurred in 173 (28%) patients including 110 Hymenoptera stings – mild 39, moderate 62 and severe 9. From primary hospitals, 53(9%) cases had been transferred to tertiary care units for further management. Of them, 41 cases were Hymenoptera stings and 24 (58%) of them had mild, moderate to severe anaphylaxis. In the entire group, 27% severe cases received adrenaline. Conclusions: The primary hospitals in NW province of Sri Lanka manage large numbers of arthropod stings and bites. These include Hymenoptera (hornet and bee), centipedes, spiders, and scorpions. Pain, swellings and anaphylactic reactions were the most common adverse effects.